Encephalitozoon: Tissue Culture, Cryopreservation, and Murine Infection. Issue 1 (16th November 2018) - Han, Bing; Moretto, Magali; M. Weiss, Louis
Abstract: Microsporidia are eukaryotic unicellular parasites that have been studied for more than 150 years. They are found throughout the world and are capable of infecting various invertebrate and vertebrate hosts. They can cause disease in both immune‐compromised and immune‐competent humans. In immune‐compromised individuals, infections can be severe and often fatal. Microsporidia possess a unique, highly specialized invasion mechanism that involves a structure known as the polar tube as well as the spore wall. During spore germination, the polar tube rapidly discharges from the spore and deliver the sporoplasm into the host cell. Spores are the only stage of microsporidia that can survive outside of host cells. Since the first attempt to culture microsporidia in vitro in 1930s, their cultivation has served a critical role in the study and diagnosis of these parasites. In this chapter, we include methods on the cultivation, isolation, and cryopreservation of Encephalitozoon cuniculi, which can infect humans and provides a useful model for other microsporidia. These methods can also be utilized for the culture of Encephalitozoon hellem or Encephalitozoon intestinalis . © 2018 by John Wiley & Sons, Inc.